2021
DOI: 10.1002/psc.3295
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of major tryptophyllin L peptides: A joint investigation of Gaussian‐based 3D‐QSAR and radical scavenging experiments

Abstract: The red tree frog Litoria rubella from Australia has been studied for several decades showing that their dorsal skin glands secrete a number of small peptides containing a Pro–Trp sequence, known as tryptophyllin L peptides. Although peptides from many genera of Australian frogs have been reported to possess a variety of biological activities, the bioactivities of this peptide family have remained to be discovered. In this study, we investigated the antioxidant potency of a number of tryptophyllin L peptides f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The effect of amidation was found inconsistent with that of the previous study. 24 While predictions from the present models indicated that amidation moderately increased ABTS + Á scavenging ability (Table 4), experimental results showed an opposite trend for two pairs of tripeptides (PWY, PYW, and their amidated counterparts; Figure 5).…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 57%
See 4 more Smart Citations
“…The effect of amidation was found inconsistent with that of the previous study. 24 While predictions from the present models indicated that amidation moderately increased ABTS + Á scavenging ability (Table 4), experimental results showed an opposite trend for two pairs of tripeptides (PWY, PYW, and their amidated counterparts; Figure 5).…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 57%
“…The results were not in agreement with those from the previous study as F-P-W-L(NH 2 ) and P-W-L(NH 2 ) displayed higher TEAC values than their acidic derivatives both experimentally and statistically. 24 Therefore, it can be concluded that amidation does not affect ABTS + Á scavenging abilities of peptides significantly or other factors may overrule this effect. The TEAC values of the five peptides and GSH over a concentration range from 2.5 to 10 μM at 6 min was compared in Figure 7.…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 99%
See 3 more Smart Citations